2009
DOI: 10.1002/erv.944
|View full text |Cite
|
Sign up to set email alerts
|

User satisfaction with services in a randomised controlled trial of adolescent anorexia nervosa

Abstract: Background: User satisfaction is a neglected outcome in adolescent anorexia nervosa especially since the relative effectiveness of different treatments is unclear. It may also affect clinical outcome. Aims: To assess young person's and parents' satisfaction with CAMHS outpatient, specialist outpatient and inpatient treatment received in a large randomised controlled trial. Method: Quantitative and qualitative analysis of questionnaire data from 215 young people and their parents followed by focus groups to fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 13 publications
3
52
1
2
Order By: Relevance
“…This factor has long been recognised as important in psychotherapy research as a variable explaining a large proportion of the outcome variance (Messer & Wampold, 2002). These findings agree with those of previous qualitative studies which identified that ED sufferers value empathy and understanding in clinical encounters (De la Rie et al, 2008; Roots, Rowlands, & Gowers, 2009; for review see Bell, 2003). Personal qualities of staff did not make it into the overall ‘top five’ quality criteria among US carers and professionals, but in both these groups a sizeable proportion of participants (US carers: 17.9%; US professionals 18.6%) mentioned this category as important.…”
Section: Discussionsupporting
confidence: 91%
“…This factor has long been recognised as important in psychotherapy research as a variable explaining a large proportion of the outcome variance (Messer & Wampold, 2002). These findings agree with those of previous qualitative studies which identified that ED sufferers value empathy and understanding in clinical encounters (De la Rie et al, 2008; Roots, Rowlands, & Gowers, 2009; for review see Bell, 2003). Personal qualities of staff did not make it into the overall ‘top five’ quality criteria among US carers and professionals, but in both these groups a sizeable proportion of participants (US carers: 17.9%; US professionals 18.6%) mentioned this category as important.…”
Section: Discussionsupporting
confidence: 91%
“…, Roots et al . ). Whilst therapeutic alliance is not a specific therapy in itself, therapeutic alliance accounts for improved consumer outcomes in mental health care (Howgego et al .…”
Section: Discussionmentioning
confidence: 97%
“…Three subscales measure perceived criticism, perceived emotional involvement and perceived warmth. The scale is completed separately for each participating carer (baseline, 6 months). The Treatment Satisfaction Questionnaire (Roots, Rowlands, & Gowers, ) is an established instrument rating prior expectation of, and motivation to participate in, treatment they have received (randomised or not) on a Likert scale. The measure includes an area for free expression about any aspect of the services they have received (baseline, 6 months). The Client Service Receipt Inventory (CSRI) is a well‐established interview method of data collection, linked to cost analysis (Beecham & Knapp, ).…”
Section: Methods and Designmentioning
confidence: 99%